Surgical Indications for Diverticulitis in Germany: Are All Operations Justified? - Schildberg, C. W.; Schellerer, Vera; Croner, R.; Oberländer, H.; Hohenberger, Werner (Zentralblatt für Chirurgie, 2015)
Pathological changes of preexisting sigma diverticulosis into a state of sigma diverticulitis are possible. Treatment of sigma diverticulitis accounts for a significant proportion of emergency treatments in clinics. The number of patients treated for sigma diverticulitis has risen steadily in recent years. Although it can be observed that operated cases making 7 % compared with 14 % to all stationary admissions, there is a less marked increase. Nevertheless, the question should be clarified as to how high the proportion of complicated surgical cases is in relation to non-complicated cases. It is important to clarify, in this context, if each operation is justified or whether in some cases there is over-treatment.All data relating to Germany, were prospectively collected by the treating hospitals using the DRG and evaluated by the Federal Statistical Office. The treatment numbers from Erlangen were prospectively collected from the encrypted DRG and analysed retrospectively by the coding officer. The investigated period lasted from 2005 to 2010. To demonstrate some treatment options, the following possible forms of therapy were examined with reference to the Hansen/Stock classification.In Germany, about 40 % of stationary patients with sigma diverticulitis are treated surgically. It is striking that in about two thirds of all operated patients uncomplicated forms of diverticulitis were present. The remainder consisted of covered or free perforations. For these complicated forms, various treatment approaches have been established. Ultimately, in dependence of timing these are always surgically treated. In the milder forms the general indication for surgery has come into discussion as the recommendation for a surgical approach after the second relapse in the symptom-free interval is being questioned by several groups based on the age of the studies on which the recommendations are based.A significant increase in hospital admissions and surgically treated patients is demonstrated. Striking was that a closer analysis of data revealed that mainly non-complicated cases were surgically treated. This should be seen as a clear indication for an over-treatment. Therefore, possibly not all surgeries performed are justified. In the case of complicated forms, in consideration of various treatment paths, surgery is inevitable in most cases.
EVALuna2:15137